Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - Chapters 1-7 Cumulative Review Problem Set - Page 324: 6



Work Step by Step

Substituting the value $x=-9$ into the expression and then simplifying, we obtain: $x^{2}+5x-36$ =$(-9)^{2}+5(-9)-36$ =$81-45-36$ =$81-81$ =$0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.